Mathematical model development for predicting the number of road traffic accidents involving personal mobility devices - Anastasiya A. Yung (Вестник СибАДИ)
Introduction. Over the past seven years, the demand for the use of personal mobility devices (PMDs) has grown significantly. However, behind the popularity of these transport means is a rapid increase in the number of road accidents. In order to assess the changes of the situation in the field of accidents involving application of individual mobility devices on the scale of Moscow, a mathematical model was developed to predict the impact of the number of individual vehicles on accidents, namely road accidents.Materials and methods. This article presents the results of mathematical modeling based on the influence of the number of personal mobility devices (PMDs) on the number of accidents involving them. To achieve these results, the science of econometrics was applied, which studies quantitative and qualitative economic relationships using statistical and other mathematical methods and models, as well as regression analysis, which allows us to study the effects of one independent variable on the dependent one. The statistical significance of the regression equation as a whole and individual regression and correlation parameters was assessed.Results. The mathematical model has been created to predict the number of accidents involving personal mobility devices (PMDs) for Moscow, depending on the number of this type of moving vehicles on the street and road network.Discussion and conclusion. The use of the given model will let with the help of linear equation of paired regression predict the number of road accidents depending on the quantity of personal mobility devices (PMDs) on the street and road network, which will allow for a certain probability to assert the increase in accidents involving these types of transport devices.